Analysis of Furnace Gases.-Description of the Orsat Apparatus - T. Prof. Egleston (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1874)
ALL industrial establishments whose operations depend upon chemical reactions use gases. In the simplest case the oxygen of the atmosphere, heated or not, as the case may be, is used, and in other cases, gases which are produced by a special apparatus of more or less complex composition. The manufacturer depends, for the success of his operations, entirely upon having these gases arrive at the right time, in the proper proportions, at the required temperature. It often requires but a slight variation in their composition to make a given process a success or a failure. In most cases the gas used is formed from fuel, and according as variations in its composition are produced by alterations in the manner of charging the grate, not only different, but often directly opposite, results are obtained. The great industrial question of the present time, and one upon which the prosperity of the world depends, is how to get the greatest amount of useful effect from fuel, whether the caloric is used directly or is transformed into horse-power. In almost all industrial pursuits this translates itself into the question of how to construct a fireplace and its adjuncts in such a way that the heat of the flame and of the products of combustion shall be made to produce a maximum effect. Unfortunately, until very recently, except by comparison, there was no means of ascertaining whether the loss of useful effect was 80, 40, or 20 per cent. of the total amount of fuel employed. It seems now strange that there should have been furnaces so constructed as to produce 20 per cent. of carbonic acid in the fireplace, but this has been proved by analysis to have been true. It does seem incredible that, notwithstanding the immense number and variety of furnaces used for different processes, and the great difference in kind, quality, and quantity of fuels consumed, there should formerly have been used for them all, the same stereotyped fireplace, varied only in its dimensions of height, length, and breadth. It is true that, with a good fireman, excellent effects may be, and have been, produced, but the manufacture is here, as in many other cases, dependent on the intelligence of the workman, a very uncertain reliance for capital to rest upon. The workman, unless he receives a prime for fuel saved, or is fined for excessive use of it, may be said